2020
DOI: 10.1186/s12882-020-02114-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient willingness to accept hepatitis C-infected kidneys for transplantation

Abstract: Background As organs infected with Hepatitis C virus (HCV) provide an opportunity to expand the donor pool, the primary aim of this study is to explore patient willingness to accept a kidney from HCV-infected donors compared to other high-risk donors. Methods An anonymous, electronic survey was sent to all active kidney transplant waitlist patients at a single large volume transplant center. Patients were asked to respond to three hypothetical organ offers from the following: 1) HCV-infected donor 2) Donor w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Patients and providers appear concerned with DAA costs and insurance coverage, a recurring theme in all of the studies reviewed. Patients demonstrated worry about whether insurance would cover their copays 9,19 and expressed apprehension towards the increased number and frequency of office visits required for HCV treatment initiation and monitoring 14,19 . Providers noted concerns regarding high costs both to the patient and to the program 10 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients and providers appear concerned with DAA costs and insurance coverage, a recurring theme in all of the studies reviewed. Patients demonstrated worry about whether insurance would cover their copays 9,19 and expressed apprehension towards the increased number and frequency of office visits required for HCV treatment initiation and monitoring 14,19 . Providers noted concerns regarding high costs both to the patient and to the program 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients demonstrated worry about whether insurance would cover their copays 9,19 and expressed apprehension towards the increased number and frequency of office visits required for HCV treatment initiation and monitoring. 14,19 Providers noted concerns regarding high costs both to the patient and to the program. 10 These concerns appear justified: although 73.2% of post-transplant patients surveyed did not pay a copay, 16.3% found costs were higher than anticipated; and of patients with a household income of < $20 000, some copay was still required for 20%.…”
Section: Cost and Insurance Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of transplant programs are accepting these kidneys, 9 either in the setting of clinical trials 5–8 or in real‐world settings 4,10 . Moreover, a study of decision‐making by HCV‐naĂŻve candidates suggested that most were willing to accept HCV‐infected kidneys under at least some circumstances, such as a kidney from a young donor 11,12 . A single‐center trial and national cohort studies using OPTN registry data have demonstrated that 1‐year allograft function after transplantation is similar between recipients of HCV‐infected kidneys and recipients of kidneys from matched donors without HCV 4,5,9,13 .…”
Section: Introductionmentioning
confidence: 99%
“…4,10 Moreover, a study of decision-making by HCV-naĂŻve candidates suggested that most were willing to accept HCV-infected kidneys under at least some circumstances, such as a kidney from a young donor. 11,12 A singlecenter trial and national cohort studies using OPTN registry data have demonstrated that 1-year allograft function after transplantation is similar between recipients of HCV-infected kidneys and recipients of kidneys from matched donors without HCV. 4,5,9,13 However, important concerns have emerged suggesting that donor-derived HCV viremia might be associated with unexpected immunological complications such as BK polyomavirus (BKPyV) infection.…”
Section: Introductionmentioning
confidence: 99%